Towards Equal Opportunities: The Municipality of Goicoechea and the National Disability Policy 2011-2030 - Cruz Astorga, Jovanna (2025)
Introduction: The Local Equal Opportunity Policy of the Municipality of Goicoechea responds to the institutional demand placed in the National Disability Policy (PONADIS) 2011-2030, to continue the work for the inclusion of people with disabilities in society and the elimination of barriers to their full participation. Objective: To describe the existing link between the approach to disabilities in the various population groups of the canton of Goicoechea, the actions of its municipality and the guidelines established in the PONADIS 2011-2030. Method and technique: Structured interviews were applied to a sample of seven strategic officials in terms of the PLEO of the Municipality of Goicoechea; in addition to content analysis and non-participant observation. The data were analyzed according to an exploratory qualitative approach, in order to know the form and nature of the social reality of people with disabilities in the canton. Results: a) Coherence and efficiency in the local management of resources, knowledge and approach to the needs of people with disabilities were identified, as well as, b) the congruence between the fundamental axes, goals and objectives of the PONADIS 2011-2030 with the municipal management of social services. Conclusion: The process demonstrated the efforts made in the actions linking the local approach to disabilities and PONADIS.